HLA antigens in coeliac disease associated with malignancy. Issue 10 (October 1983) - Swinson, C M; Hall, P J; Bedford, P A; Booth, C C
Abstract : Coeliac patients are at greater risk than the general population of developing malignant neoplasms, particularly lymphomas. The establishment at the Clinical Research Centre of a national collaborative study of coeliac patients with malignancy provided the opportunity to carry out HLA typing for 55 HLA-A, B and C and the 10 recognised DR antigens on a group of coeliac patients with malignancy. Study of a sample of 44 patients with biopsy proven coeliac disease and histologically confirmed malignancy, including 12 with malignant histiocytosis, and 57 coeliac patients without malignancy, failed to show any significant differences in antigen frequencies between patients with and without malignancy. These results indicate that there are no HLA genetic markers associated specifically with the development of malignancy in coeliac disease.